Pengaruh Periklanan Dan Personal Selling Terhadap Keputusan Pembelian Skincare Tabita Di Kota Langsa - Auvitta, Yosi; Junaida, Erni; Indah, Dewi Rosa (Universitas Labuhanbatu, 2022)
This study aims to examine the impact of advertising and personal selling on the purchasing decisions of Tabita Skincare in Langsa City. This survey uses a sample of 96 respondents. The analytical method used is multiple linear regression analysis, t-test, F-test, and coefficient of decision analysis. Total t-test proves that advertising factor has no significant impact on purchasing decisions for Tabitha Skin Care in Langsa City, and personal selling has a significant impact on purchasing decisions for Tabitha Skin Care in Langsa City. Total F test proves advertising and personal selling factors simultaneously significant effect on purchasing decisions for tabitha skin care in Langsa City. The results of the coefficient of determination test yielded a value of 0,744 or 74,4% of the advertising and personal selling variables influencing the purchasing decision of skin care, while the remaining 25,6% was influenced by other variables not examined in this study.